Improving student learning outcomes in science subjects through the implementation of PBL-based module - Eva Nursa’ban; Mohammad Masykuri; Sri Yamtinah (University of Muhammadiyah Malang, 2019)
Problem-based learning (PBL) has been reported as one of the learning models which can improve student learning outcomes optimally. Unfortunately, the frequency of implementing PBL and the teacher knowledge level about PBL is not optimal yet. This quantitative descriptive study aimed at determining the effect of PBL-based modules implementation on student learning outcomes. The population of this study was the XI grade students of SMAN 2 Wera in which the sample was the students of XI-Natural Science Class. Test was chosen as an instrument in the data collection process which was given at the beginning and the end of the implementation. The dependent-test was performed, after collecting the data. The study results indicated that the student learning outcomes increased significantly. Therefore, the application of PBL-based module is recommended to be carried out during science learning of XI graders.